The concept and significance of corporate disputes: national and foreign experience - Uktamov Umidjon Shavkat o’g’li (Zien Journals, 2023)
The article deals with the issues of jurisdiction of corporate disputes, the concept and meanings, as well as foreign experience in resolving corporate disputes
Keywords: corporate dispute; founder; conflict; owner